GOALS OF PROFESSIONAL DEVELOPMENT OF TEACHER TRAINING UNIVERSITY STUDENTS AND TEACHERS-PRACTITIONERS:THE SURVEY RESULTS - Klavdiya K. Golubushina; Irina A. Vinogradova; Olga I. Klyuchko; Elena V. Samosadova (Высшее образование в России)
The article presents the theoretical and empirical data about the a goal as an indicator of life perspectives and as a professional activity’s component. The results of the survey on goals of professional development of students of pedagogical universities and teachers are also presented. The authors came to a conclusion that there is an evident problem of outprofessional tendency of future teachers, and the problems of object-oriented self-relationship and the lack of lifelong goals for the professional development typical for teachers-practitioners. The revealed problems can be viewed as the features of the dysontogenesis of the professional formation.